Posted by dee on Tuesday, July 31, 2012 at 2:51am.
4 x + 3 y = 0
16 x + 3 = 8y
______________
Multiply the first equation by 4
16 x + 12 y = 0
16 x + 3 = 8y
______________
Subtract 8 y by second equation
16 x + 12 y = 0
16 x + 3 - 8 y = 8y - 8y = 0
______________
16 x + 12 y = 0
16 x + 3 - 8 y = 0
______________
Subtract 3 by second equation
16 x + 12 y = 0
16 x + 3 - 8 y - 3 = 0 - 3
______________
16 x + 12 y = 0
16 x - 8 y = - 3
________________
Subtract fsecond equation from first equation
16 x - 1 6 x + 12 y - ( - 8 y ) = 0 - ( - 3 )
12 y + 8 y = 3
20 y = 3 Divide both sides by 20
y = 3 / 20
Put y = 3 / 20 in first equation.
4 x + 3 y = 0
4 x + 3 * 3 / 20 = 0
4 x + 9 / 20 = 0 Subtract 9 / 20 by both sides
4 x + 9 / 20 - 9 / 20 = 0 - 9 / 20
4 x = - 9 / 20 Divide both sides by 4
x = - 9 / ( 20 * 4 )
x = - 9 / 80
Solution :
x = - 9 / 80 , y = 3 / 20